2017
DOI: 10.1002/anie.201701790
|View full text |Cite|
|
Sign up to set email alerts
|

The Interstitial Carbon of the Nitrogenase FeMo Cofactor is Far Better Stabilized than Previously Assumed

Abstract: The first quantum-mechanical calculations of all relevant potential constants in both the iron-molybdenum cofactor and the iron-vanadium cofactor of nitrogenase suggest that the carbide is bound to the center of the enzyme much more strongly than hitherto assumed. Previous studies seemed to indicate a dummy function of the interstitial carbon, with a weak force constant (ca. 0.32 N cm ). Our new investigations confirm a different picture: the central carbon atom binds the iron-sulfur cluster through six covale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
(33 reference statements)
2
30
0
Order By: Relevance
“…Typically, smaller model systems are used to study particular active sites such as in the calculations on both the FeMo- and FeV-cofactors performed by Grunenberg in 2017 to investigate the potential force constants of the interstitial carbide atom. 384 Scott et al published a study on the effects of CO-inhibition on the Mo-nitrogenase active site using both spectroscopy and DFT. 385 Similarly, Siegbahn et al claimed that the central carbon in the FeMo-cofactor becomes protonated during the nitrogen fixing process.…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“…Typically, smaller model systems are used to study particular active sites such as in the calculations on both the FeMo- and FeV-cofactors performed by Grunenberg in 2017 to investigate the potential force constants of the interstitial carbide atom. 384 Scott et al published a study on the effects of CO-inhibition on the Mo-nitrogenase active site using both spectroscopy and DFT. 385 Similarly, Siegbahn et al claimed that the central carbon in the FeMo-cofactor becomes protonated during the nitrogen fixing process.…”
Section: Mechanistic Complexity In Catalysis By 3d Transition Metalsmentioning
confidence: 99%
“… reviews this work, and, on the basis of DF calculations of Mossbauer isomer shifts, and X‐ray absorption spectroscopy, concludes that the charge z on the core cluster [CFe 7 MoS 9 ] z is −1. All recent calculations are consistent with this overall redox level . Although the value of assignment of individual oxidation states to the metal atoms of FeMo‐co is questionable, there is experimental evidence from spatially resolved diffraction refinement of the anomalous scattering of the seven Fe atoms in resting FeMo‐co that Fe1, Fe3 and Fe5 are more reduced that the other four …”
Section: Charge Statesmentioning
confidence: 99%
“…Benediktsson and Bjornsson discussed in detail the results of QM/MM investigations of the three BS7 states of resting FeMo‐co, concluding in favour of BS7‐1 . Thus there is general agreement that the BS7 electronic states best describe the S =3/2 resting state of FeMo‐co: BS7‐2 [+−+−++−] is generally used …”
Section: Calculation Of Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In the proposed base pair structure, both Hg(II) ions are coordinated by an endocyclic nitrogen atom of εA and an exocyclic oxygen atom of the thymine residue [ 80 ]. This structure ( Scheme 9 ) differs slightly from the originally proposed one containing one additional bond from the endocyclic nitrogen atom of thymine to one of the Hg(II) ions, because a calculation of the Hg···N force constant [ 81 ] had resulted in an exceptionally low value of 0.7 N cm −1 [ 80 ]. A re-inspection of the originally proposed structure indicated that it represents a local energy minimum rather than the global one.…”
Section: Reviewmentioning
confidence: 99%